Analysis of aided thresholds in children who have undergone cochlear reimplantation: a ten-year follow-up - da Costa, Lucas Bevilacqua Alves; Vicente, Leticia Cristina; do Nascimento Silva, Leandra Tabanez; Alvarenga, Kátia Freitas; Salgado, Manoel Henrique [UNESP]; Costa, Orozimbo Alves; Brito, Rubens (FapUNIFESP (SciELO), 2023)
Purpose: To characterize hearing thresholds at frequencies of 500, 1000, 2000 and 4000 Hz in children undergoing reimplantation with a follow-up of at least 10 years. Methods: Retrospective review of medical records of children who underwent reimplantation surgery for at least 10 years. The auditory thresholds obtained in free-field pure tone audiometry with the cochlear implant were evaluated at frequencies of 500, 1000, 2000 and 4000 Hz at four different times: 1 (before failure), 2 (activation), 3 (five years after reimplantation) and 4 (ten years after reimplantation, regardless of the time of use of the 2nd CI) in patients with a follow-up of at least 10 years. Results: Evaluating patients who underwent reimplantation, it was observed that the thresholds of 500, 1000, 2000, 4000 Hz were similar in the long term to those obtained in patients who were implanted only once, thus not presenting damage in the detection of sounds. Conclusion: Reimplantation had no long-term effect on the hearing thresholds obtained in children who underwent this surgery due to internal component failure.
Análise de limiares tonais de crianças submetidas ao reimplante: seguimento de 10 anos
Keywords: Audiometry; Children; Cochlear Implant; Hearing; Pure-Tone; Reimplantation